Severity of Peronospora variabilis Gäum. in five cultivars of Chenopodium quinoa Willd. under field conditions in La Molina - Ramírez Maguiña, Héctor Andrés (2020)
The objective of this research was to evaluate the behavior of five commercial varieties of quinoa, naturally infected by P. variabilis. The study was carried out at the Universidad Nacional Agraria La Molina, Lima, Peru. The varieties studied were: Amarilla de Maranganí (AMR), Pasankalla (PAS), Negra Collana (NGR), Salcedo (SAL), and Altiplano (ALT). Treatments were distributed in a complete randomized block design with five repetitions. Variables evaluated include: yield (kg/ha), plant height (cm), disease severity using Area under Disease Progress Curve (AUDPC), protein content (%), weight of one thousand grains (g) and grain size (%). Comparisons of means were conducted using Tukey’s test, Pearson correlation coefficient analysis and statistical significance was set at p < 0,05. Results revealed statistics differences among treatments. The AMR variety had the highest yield (2628,1 kg/ha) followed by PAS (2201,9 kg/ha), NGR (1408,6 kg / ha), SAL (1244,4 kg / ha) and AL (649,2 kg/ha). The most susceptible variety to downy mildew was ALT (AUDPC = 4771,6), followed by SAL (4337,7), NGR (3796,3), PAS (3377,2) and AMR (2364,1). The correlation analysis of AUDPC showed a significant negative correlation with plant height (r = -0,94), yield (-0,88), and the percentage of large grains (-0,81). In conclusion, AMR was the variety with the best yield and the one that showed a high tolerance to downy mildew, while ALT had the lowest yield and was the most susceptible variety.